2018
DOI: 10.1080/20008198.2018.1463794
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative symptoms mediate the relation between PTSD symptoms and functional impairment in a sample of military members, veterans, and first responders with PTSD

Abstract: Background: Posttraumatic Stress Disorder (PTSD) is associated with significant functional impairment in important areas, including interpersonal relationships and occupational or educational roles. Preliminary evidence suggests that the dissociative subtype of PTSD (PTSD+DS), characterized by marked symptoms of depersonalization and derealization, is associated with increased functional impairment and disease severity, including among military members and veterans diagnosed with PTSD. Similarly, first respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 93 publications
1
39
0
1
Order By: Relevance
“…Investigation of the different aspects of PPS representation (function, plasticity and dynamics, neural correlates) in psychopathology can deepen our scientific and clinical understanding of bodily self-consciousness, particularly in relation to the altered states of consciousness that underlie dissociative symptoms characterizing certain psychological disorders, including trauma-related disorders. Depersonalization and derealization symptoms remain among the most difficult psychological symptoms to recognize, diagnose, and treat, despite seriously impacting the quality of life of individuals ( Boyd et al, 2018 ). A greater understanding of the PPS representation in trauma-related disorders has the potential to lead to innovative diagnostic methods for recognizing dissociative symptoms, as well as the development of novel clinical interventions designed to specifically target these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the different aspects of PPS representation (function, plasticity and dynamics, neural correlates) in psychopathology can deepen our scientific and clinical understanding of bodily self-consciousness, particularly in relation to the altered states of consciousness that underlie dissociative symptoms characterizing certain psychological disorders, including trauma-related disorders. Depersonalization and derealization symptoms remain among the most difficult psychological symptoms to recognize, diagnose, and treat, despite seriously impacting the quality of life of individuals ( Boyd et al, 2018 ). A greater understanding of the PPS representation in trauma-related disorders has the potential to lead to innovative diagnostic methods for recognizing dissociative symptoms, as well as the development of novel clinical interventions designed to specifically target these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dissociative subtype of PTSD is rarely seen in whiplash-associated disorder, 18 whereas pronounced levels of dissociation have been seen in complex PTSD. 3 Subjects with accident-related or whiplash-associated PTSD conditions may show more pronounced levels of anxiety and pain catastrophizing, and lower levels of dissociation. 18 It has been shown that experimental pain ratings are negatively related to dissociation levels, 7 and positively related to anxiety associated with fearful appraisals of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, other studies analyzed the potential relationships among traumatic events, PTSD and depression in groups of subjects exposed to completely different types of recurrent or chronic traumatic events, including student military veterans, 43 homeless women with mental illnesses, 44 refugees and asylum seekers, 45 or Korean fire fighters. 46 Other studies highlighted clinical similarities between PTSD and depression, as demonstrated in samples of inpatients with PTSD, 47 community samples, 48 Vietnam veterans, 49 underground train drivers, 50 military members, veterans, and first responders (eg, police, fire, and paramedics) with probable PTSD, 51 or survivors of a chemical warfare. 52 Taken as a whole, all these studies pointed out to the substantial symptoms' overlap between the two disorders, to the impact on psychosocial and occupational levels, and to the low treatments' response.…”
Section: Discussionmentioning
confidence: 99%